2022
DOI: 10.38021/asbid.1162204
|View full text |Cite
|
Sign up to set email alerts
|

Spor Lisesi Öğrencilerinin Beden Eğitimi Dersine Yönelik Tutumlarının İncelenmesi

Abstract: Araştırma spor lisesi öğrencilerinin beden eğitimi dersine yönelik tutumlarının incelenmesi amacıyla yapılmıştır. Araştırmanın evren ve örneklemini 2021-2022 eğitim-öğretim yılında Denizli Spor Lisesinde 9-10-11-12. Sınıflarında öğrenim gören ve araştırmaya gönüllü katılan toplamda (90 kadın, 124 erkek) 214 öğrenci oluşturmaktadır. Araştırmada veri toplama aracı olarak araştırmacı tarafından oluşturulan kişisel bilgi formu ile Güllü ve Güçlü (2009) tarafından geliştirilen “Ortaöğretim Öğrencileri için Beden Eğ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…In contrast to our study, Dereceli [17] discovered that the attitudes of students towards physical education differed based on their status as licensed athletes or not. Dereceli's research specifically focused on female students studying at İmam-Hatip high school and Hazar [24] examined students in secondary education. In both studies, it was observed that the mean attitudes of licensed athletes were higher than those of unlicensed athletes.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to our study, Dereceli [17] discovered that the attitudes of students towards physical education differed based on their status as licensed athletes or not. Dereceli's research specifically focused on female students studying at İmam-Hatip high school and Hazar [24] examined students in secondary education. In both studies, it was observed that the mean attitudes of licensed athletes were higher than those of unlicensed athletes.…”
Section: Discussionmentioning
confidence: 99%